Influence of Hydrodynamic Conditions on Micromixing in Microreactors with Free Impinging Jets - Rufat Sh Abiev; Alexey A Sirotkin (Fluids, 2020)
An experimental study and mathematical modeling of micromixing in a microreactor with free impinging jets (MRFIJ) with a diameter of 1 mm was carried out. In the experimental part, the iodide-iodate technique was used (involving parallel competing Villermaux–Dushman reactions with the formation of I3−). Theoretical assessment revealed that more than 50% of the introduced energy is dissipated in the jets collision region. Through the use of differentiated sampling, an uneven quality distribution of micro mixing in the central and peripheral zones of the reactor was found: at moderate flow rates (700–1000 mL/min, jets velocity of 15–21 m/s) the micromixing in the central part of reactor is up to 12 times better than that in the periphery. Furthermore, the weight fraction of the probes in the central zones of MRFIJ is reduced with increasing jet velocity; this effect is attributed to a more intense formation of ligaments and droplets upon collision of jets and their secondary mixing on the walls of the apparatus. In terms of the weighted average concentration, the best quality of micromixing in the samples is achieved at a flow rate of 300 mL/min. With an increase in the flow rate (and velocity) of the jets, the dependence of the I3− concentration on the flow rate has a nonmonotonic character, which is explained by a change in the nature of the flow in the collision zone of the jets: the transition from the formation of a liquid sheet to the intensive formation of ligaments and drops and secondary mixing of the liquid film formed on the walls of the reactor. The effect of “freshness” of solutions on the concentration of reaction products was studied.